2020
DOI: 10.1167/iovs.61.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Clinical Biomarkers and Optical Coherence Tomography Angiography Parameters in Type 2 Diabetes Mellitus

Abstract: Citation: Choi EY, Park SE, Lee SC, et al. Association between clinical biomarkers and optical coherence tomography angiography parameters in type 2 diabetes mellitus. Invest Ophthalmol Vis Sci. 2020;61(3):4. https://doi.org/10.1167/iovs.61.3.4 PURPOSE.To investigate the clinical significance of the changes in the macular microvasculature in patients with diabetes mellitus type 2 without diabetic retinopathy. METHODS.Fifty-five patients with diabetes mellitus type 2 without diabetic retinopathy and 48 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 38 publications
(55 reference statements)
3
15
1
2
Order By: Relevance
“…Moreover, we also found a smaller area and perimeter of the FAZ in patients with stroke. Our findings seemed to be different from the other studies showing an enlarged FAZ area in patients with diabetes mellitus, which is one of the major risk factors of stroke (Choi et al, 2020 ). One of the possible reasons was the sex distribution of our patients with stroke.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, we also found a smaller area and perimeter of the FAZ in patients with stroke. Our findings seemed to be different from the other studies showing an enlarged FAZ area in patients with diabetes mellitus, which is one of the major risk factors of stroke (Choi et al, 2020 ). One of the possible reasons was the sex distribution of our patients with stroke.…”
Section: Discussioncontrasting
confidence: 99%
“…In a previous study, hypertension showed no correlation with retinal capillary density 32 . In another report, the VD of the SCP was negatively correlated with systolic blood pressure, and no correlation was found in the VD of the DCP with all systemic factors 33 . The correlation of retinal perfusion with various systemic factors seems to be controversial, therefore further studies are necessary to confirm this.…”
Section: Discussionmentioning
confidence: 83%
“…Detection of retinal dysfunction at the preclinical stage can improve the management of DR [7]. OCTA may detect retinal microvascular changes in patients with diabetes mellitus (DM) without DR [8][9][10].…”
Section: Introductionmentioning
confidence: 99%